Profile of haematological indices among pulmonary tuberculosis patients attending Kisii teaching and referral hospital, Kenya - Ongwae, Jared M.; Musyoki, Stanslaus K.; Mongare, Samuel (International Journal Of Community Medicine And Public Health, 2023)
Background: Tuberculosis, caused by Mycobacterium tuberculosis, affects approximately 10 million people worldwide, with an annual global mortality rate of 1.4 million (WHO, 2021). This study aimed to profile hematological indices among pulmonary tuberculosis patients at Kisii teaching and referral hospital, Kenya from February 2022 to July 2022 where Kisii County reports around 1800 TB cases annually. Methods: A cross-sectional study design with 210 participants was used, 105 patients and 105 controls. Venous blood was collected in ethylene diamine tetra acetic and analyzed using flow cytometry technique. Erythrocyte sedimentation rate was set by use of Westergren technique while a thin blood film was prepared for microscopic examination of cells. Data obtained was analyzed using Stata version 23. Results: Female patients accounted for 55 (52.5%) of positive cases while males accounted for 50 (47.5%). PTB patients showed significantly lower RBC count, HGB, HCT, MCH, and MCHC compared to controls (p=0.001). ESR was significantly higher in PTB patients (p=0.001). PTB patients had higher platelet count and total WBC count (p=0.009 and p=0.018, respectively) with increased neutrophil and monocyte counts (p=0.044 and p=0.041, respectively). No significant differences were observed in lymphocyte counts (p=0.086). Conclusions: The study identified significant hematological abnormalities in pulmonary tuberculosis patients, including normocytic normochromic anemia, toxic granulation in white blood cells, and thrombocytosis, highlighting these as potential diagnostics and clinically significant hematological parameters in the management of pulmonary tuberculosis.